Educational Technology that Transforms: Educators' Transformational Learning Experiences in Professional Development - Kathleen P. King (Adult Education Research Conference, 2000)
Research conducted among 175 teachers engaged in learning educational technology reveals that transformational learning provides insights into their experiences of learning to use technology in their teaching. As facilitators and themes of perspective transformation are presented, recommendations for faculty development in educational technology are discussed.